THE EFFECT OF ANAEROBIC FATIGUE ON PROPRIOCEPTION IN ADOLESCENT FEMALE BASKETBALL PLAYERS ANAEROBİK YORGUNLUĞUN ADÖLESAN KIZ BASKETBOL OYUNCULARINDA PROPRIOSEPSIYON ÜZERİNDEKİ ETKİSİ - Kiliç S.; ALPAY K.; Atici E.; SOYAL M.; Inal-Gültekin G. (My University, 2025)
Purpose: Muscle fatigue is known to alter the proprioceptive system, the central proprioception process, and power generation capacity. This study aims to determine the effect of anaerobic fatigue on lower-extremity proprioception in adolescent female basketball players. Methods: The study included licensed female basketball players (n=30) between the ages of 12 and 16. Their dominant lower extremities were evaluated for knee joint position-sense measurements. Active and passive knee joint position senses were measured with an isokinetic dynamometer at 30° and 60° degrees prior to, immediately after anaerobic fatigue, and finally after 10 minutes of the recovery period. The Wingate Anaerobic Strength Test was used to induce anaerobic fatigue. We documented the knee joint position sense of each participant. Results: Following a 30-second anaerobic fatigue, a significant reduction in the sense of active joint perception at 30° and 60° knee flexion was observed compared to baseline values (p> 0.017). The knee joint\"s proprioception at 30° and 60° flexion returned to baseline levels after a 10-minute recovery from fatigue. The passive joint perception did not show any statistical changes. Conclusion: Anaerobic fatigue reduces knee proprioception in adolescent female basketball players. Moreover, proprioceptive sensitivity can return to baseline levels with a recovery time of as little as 10 minutes.
Keywords: Tıp; Dahili Tıp Bilimleri; Fiziksel Tıp ve Rehabilitasyon; Cerrahi Tıp Bilimleri; Ortopedi ve Travmatoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Physical Medicine and Rehabilitation; Surgery Medicine Sciences; Orthopedics and Traumatology; Health Sciences; Klinik Tıp (Med); Klinik Tıp; Rehabilitasyon; Ortopedi; Clinical Medicine (Med); Clinical Medicine; Rehabilitation; Orthopedics; Ortopedi ve Spor Hekimliği; Fizik Tedavi, Spor Terapisi ve Rehabilitasyon; Orthopedics and Sports Medicine; Physical Therapy, Sports Therapy and Rehabilitation; Adolescent; Basketball; Fatigue; Proprioception